Understanding Switching Behavior of Generation Z on Over The Top Video-Based Platform Using PPM Factors - Daniel Hartono; M.Y. Dwi Hayu Agustini (Soegijapranata Catholic University, 2026)
Large numbers and purchasing power of Gen z known as digital native make them a very potential market share. Over the top (OTT) providers such as Netflix have taken advantage of this potential. Research found local OTT platform Vidio took place. This research aims to understand the switching behavior of Gen z on OTT service providers using push,pull,mooring (PPM) factors that are considerably suitable to understand switching behavior in the service industry. Data were gather using a questionnaire distributed to Gen z consumers, who had switched their OTT services. SEM-PLS was applied to analyze the influence of PPM factor to switching behavior with switching intention as mediating variabel. The research results in existence of direct influence of the push and pull factors on switching behavior, but not the mooring factors. The result also implies that, in the digital era, it is easier for consumer in the service industry to switch from one service to another without first having an intention to switch. The results can help OTT service providers to better understand the consumer behavior and create retention strategies for particularly Gen Z.